Kualitas Pelayanan Pengujian Kendaraan Bermotor pada Dinas Perhubungan Kota Pangkalpinang - Lensyiana Pratiwi, Vivie; Samboteng, Lukman; Firdaus, Firdaus (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2024)
The number of public participants in motor vehicle testing at the Pangkalpinang City Transportation Service has decreased. This decline resulted from multiple factors, one among them being the level of quality of service provided. The goal of the research is to determine the quality of motor vehicle testing services at the Pangkalpinang City Transportation Service based on five dimensions, including real dimensions, reliability, responsiveness, guarantee, and empathy. The employed research method is descriptive, utilizing a quantitative approach. The analysis of data employed is the Servqual method. The research results show that the real dimension gap value is -0.316 or negative, with the weakest indicator being the availability of supporting facilities and infrastructure. The reliability dimension gap value is 0.000 or positive, with the weakest indicator being officer accuracy. The positive responsiveness dimension gap value is 0.074, and the weakest indicator is the officer's level of concern. The positiv e guarantee dimension gap value is 0.117, with the weakest indicators being the officers' skills and knowledge. The gap value for the positive empathy dimension is 0.138, with the weakest indicator being intense and effective communication. A positive gap value indicates that the dimension is in line with customer expectations, while a negative gap value indicates that the dimension is not in line with customer expectations.